Scale efficiency in European pork production - Lukas Cechura; Zdenka Zakova Kroupova; Michal Maly; Heinrich Hockmann (Review of Agricultural and Applied Economics, 2015)
The paper analyses scale efficiency in European pork production. The analysis shows significant differences in the exploitation of economies of scale among EU member states. In particular, old member states exhibit increasing returns to scale whereas most new member states show either constant or decreasing returns to scale. The differences among old and new member states are also pronounced from a dynamic perspective: whereas the old member states improved their productivity in pork production through scale efficiency, its impact in new member states was rather negative.
Keywords: D24; O12; P27; 330; pork production; scale efficiency; total factor productivity; metafrontier analysis; SFA